Prototype of a Biomimetic Multi-Spiked Connecting Scaffold for a New Generation of Resurfacing Endoprostheses - Uklejewski, Ryszard (Taylor & Francis, 2024)
The monograph comprehensively presents the research on the prototype of the biomimetic Multi-Spiked Connecting Scaffold (MSC-Scaffold) for cementless fixation of the components of a new generation of resurfacing arthroplasty (RA) endoprostheses. This research, carried out by a bioengineering-surgical team from three Polish universities, includes bioengineering design, rapid prototyping, manufacturing in selective laser melting, functionalization, surface modification, numerical studies, experimental in vitro studies, and pilot surgical experiments in an animal model. Features: Presents the prototype of the multi-spiked connecting scaffold for a new generation of resurfacing endoprostheses of the knee and the hip Explains this prototype scaffold as the first worldwide design of the biomimetic fixation of components of diarthrodial joints resurfacing endoprostheses Insights into the entire process of bioengineering design and research on this novel way of resurfacing endoprostheses fixation Reviews main results of the scaffold prototyping and SLM manufacturing, structural and osteoconductive functionalization, and surface modification Reports experimental and numerical investigations of mechanical behavior of the scaffold-bone system, cell culture studies, and pilot surgical experiments in animal models This book is aimed at professionals and graduate students in biomedical engineering, biomaterials engineering, and bone & joint surgery. The Open Access version of this book, available at http://www.taylorfrancis.com, has been made available under a Creative Commons [Attribution-Non Commercial-No Derivatives (CC-BY-NC-ND)] 4.0 license.